The innate and T-cell mediated immune response during acute and chronic gammaherpesvirus infection - Rex, Viktoria; Zargari, Razieh; Stempel, Markus; Halle, Stephan; Brinkmann, Melanie M. (Frontiers in Cellular and Infection Microbiology, 2023)
Immediately after entry into host cells, viruses are sensed by the innate immune system, leading to the activation of innate antiviral effector mechanisms including the type I interferon (IFN) response and natural killer (NK) cells. This innate immune response helps to shape an effective adaptive T cell immune response mediated by cytotoxic T cells (CTL) and CD4+ T helper cells and is also critical for the maintenance of protective T cells during chronic infection. This review focuses on the human gammaherpesvirus Epstein-Barr virus (EBV), a highly prevalent lymphotropic oncovirus that establishes chronic lifelong infections in the vast majority of the adult population. Although acute EBV infection is controlled in an immunocompetent host, chronic EBV infection can lead to severe complications in immunosuppressed patients, including post-transplant lymphoproliferative disorders (PTLD). Given that EBV is strictly host-specific, its murine homolog MHV68 is a widely used model to obtain in vivo insights into the interaction between gammaherpesviruses and their host. Despite the fact that EBV and MHV68 have developed strategies to evade the innate and adaptive immune response, innate antiviral effector mechanisms still play a vital role in not only controlling the acute infection but also shaping an efficient long-lasting adaptive immune response. Here, we summarize the current knowledge about the innate immune response mediated by the type I IFN system and NK cells, and the adaptive T cell-mediated response during EBV and MHV68 infection. Investigating the fine-tuned interplay between the innate immune and T cell response will provide valuable insights which may be exploited to design better therapeutic strategies to vanquish chronic herpesviral infection.